HUBUNGAN FAKTOR PRILAKU DENGAN KELUHAN KESEHATAN AKIBAT PAPARAN PESTISIDA PADA PETANI HORTIKULTURA DI KENAGARIAN PADANG LUA - Fajrina Hidayati (HUMAN CARE JOURNAL, 2021)
ABSTRACTPesticides are a material that is widely used in various sectors, especially in the agriculture / plantation, forestry, fishery, and food agriculture sectors. Apart from positive effects, the use of pesticides also has harmful effects on the health of its users, one of which is health complaints. The purpose of this study was to determine the relationship between behavioral factors and health complaints due to pesticide exposure to horticultural farmers in Kenagarian, Padang Lua. This research is a quantitative study with cross sectional research design, and was conducted in Kenagarian Padang Lua, Agam Regency. The sample consisted of 55 respondents. Sampling using systematic random sampling technique. Data processing used univariate analysis and bivariate analysis with the chi-square statistical test. The results showed that 56.4% of the horticultural farmers had health complaints. The results of the bivariate analysis showed that all behavioral factors were related to health complaints, namely knowledge (p = 0.010), attitude (p = 0.000), and action (p = 0.000). Knowledge, attitudes and risky actions cause health complaints to horticultural farmers in Kenagarian Padang Lua, Agam Regency. It is recommended that the local Health Service and Agricultural Extension Officers carry out agricultural extension activities regarding the correct application of pesticides and the dangers of using pesticides.Keyword: Complaints of Health, Pesticides, Horticulture FarmersABSTRAKPestisida merupakan suatu bahan yang digunakan secara luas di berbagai sektor, terutama pada sektor pertanian/perkebunan, kehutanan, perikanan, dan pertanian pangan Selain efek positif, penggunaan pestisida juga memiliki efek berbahaya bagi kesehatan penggunanya salah satunya keluhan kesehatan. Tujuan penelitian ini adalah untuk mengetahui hubungan faktor prilaku dengan keluhan kesehatan akibat paparan pestisida pada petani hortikultura di Kenagarian Padang Lua. Penelitian ini merupakan penelitian kuantitatif dengan desain penelitian cross sectional, dan dilakukan di Kenagarian Padang Lua Kabupaten Agam. Sampel terdiri dari 55 responden. Pengambilan sampel menggunakan teknik systematic random sampling. Pengolahan data menggunakan analisis univariat dan analisis bivariat dengan uji statistik chi-square. Hasil penelitian menunjukkan sebanyak 56,4% ada keluhan kesehatan pada petani hortikultura. Hasil analisis bivariat menunjukkan bahwa semua factor perilaku berhubungan dengan keluhan Kesehatan, yaitu pengetahuan (p=0,010), sikap (p=0,000), dan tindakan (p=0,000). Pengetahuan, sikap dan tindakan beresiko menyebabkan keluhan kesehatan pada petani hortikultura di Kenagarian Padang Lua Kabupaten Agam. Disarankan kepada Dinas Kesehatan dan Penyuluh Pertanian setempat agar melakukan kegiatan penyuluhan pertanian tentang aplikasi pestisida yang benar serta bahaya penggunaan pestisida.  Kata Kunci: Keluhan Kesehatan, Pestisida, Petani Hortikultura